A Hybrid Video Coder Based on Extended Macroblock Sizes, Improved Interpolation, and Flexible Motion Representation - Karczewicz, Marta; Peisong Chen; Joshi, Rajan L.; Xianglin Wang; Wei-Jung Chien; Panchal, Rahul; Reznik, Yuriy; Coban, Muhammed; In Suk Chong (IEEE transactions on circuits and systems for video technology, 2010)
This paper describes a video coding technology proposal submitted by Qualcomm in response to a joint call for proposals (CfP) issued by ITU-T SG16 Q.6 (VCEG) and ISO/IEC JTC1/SC29/WG11 (MPEG) in January 2010. The proposed video codec follows a hybrid coding approach based on temporal prediction, followed by transform, quantization, and entropy coding of the residual. Some of its key features are extended block sizes (up to 64 × 64), single pass switched interpolation filters with offsets, mode-dependent directional transforms for intra-coding, luma and chroma high precision filtering, geometric motion partitions, adaptive motion vector resolution and efficient 16-point transforms. It also incorporates internal bit-depth increase and modified quadtree-based adaptive loop filtering. Simulation results are presented to demonstrate the high compression efficiency achieved by the proposed video codec at the expense of moderate increase in encoding and decoding complexity compared to the advanced video coding standard (AVC/H.264). For the random access and low delay configurations, it achieved average bit rate reductions of 30.9% and 33.0% for equivalent peak signal-to-noise ratio, respectively, compared to the corresponding AVC anchors. The proposed codec scored highly in both subjective evaluations and objective metrics and was among the best-performing CfP proposals.